The Impact of Corporate Governance Mechanism on Fair Value Measurement in the Indonesian Banking and Financial Industries - Nugraheni, Bernadia Linggar Yekti (Jurnal Dinamika Akuntansi dan Bisnis, 2023)
Fair value is one of an important measurement since the diffusion of International Financial Reporting Standards around the world. Studies of manager opportunistic behaviors through fair value numbers in developing countries have been overlooked. This study aims to investigate the influence of corporate governance mechanism towards an opportunistic behavior through fair value measurement i.e. fair value inputs level 3. This study applied multiple regression and used samples of banking and financial companies listed in Indonesia Stock Exchange between 2015 and 2019. The corporate governance is proxied by three measurements i.e. managerial ownership, institutional ownership and audit committee educational background. This study finds that managerial ownership and institutional ownership have positive influences on fair value inputs level 3. Meanwhile, the independent commissioners and audit committee educational background have negative influences on fair value inputs level 3. Therefore, this study provides evidence that independent commissioners and audit committee educational background can reduce management opportunistic behaviors which is conducted through fair value measurement.